Report of the Working Group on Improvement of Methodology and Technology of Construction - Planning Commission (Planning Commission, 1990)
Construction must be declared as industry and treated at par with manufacturing industry for entitlement to financing facilities from banks. This would cover only the contracts of Rs. 1 Crore and above. Construction contractors should be entitled to obtain advance from scheduled and commercial banks for the purchase of plant and machinery. Further, scheduled and commercial banks should be directed to extend facilities of bill discounting and term loans for plant and machinery.
Planning Commission Government of India
Planning Commission Government of India